Polycaprolactone (PCL) / polylactice acid (PLA) reinforced with polyethlene gylcol (PEG) and nano- hydroxyapatite (n-HA) for fused deposition modeling (FDM) composite filament - Fong, Mun Kit (2021)
In this study, bio-active composite filament for fused deposition modeling (FDM) was investigated. The Polycaprolactone (PCL) and Polylactic acid (PLA) filled with Polyethylene glycol (PEG) and Nano-Hydroxyapatite (n-HA) composites were prepared by melting and compounding using Brabender Plastograph machine. The mechanical properties were assessed by tensile, flexural, and Charpy impact tests, while the thermal properties were studied via a Thermogravimetry analyser (TGA). A simulated body fluid (SBF) test was used to assess the bioactivity properties of the composites. The filament wire with the diameter of 1.75+0.05mm was fabricated using a single screw extruder. Design of experiment (DOE) software was used to find the optimum setting for inlet temperature, die temperature, spindle (screw) speed, and roller puller speed to achieve the filament wire's specific diameter. From the experiment it is found that incorporation of n-HA into PCL/PLA decreases the tensile strength and elastic modulus of both PCL/PLA/n-HA and PCL/PLA/PEG/n-HA composites. However, the incorporation of n-HA resulted in improved flexura l strength and flexural modulus but declined the composites' impact strength. On the other hand, the incorporation of PEG led into the improvement of flexural and impact strength of PCL/PLA composite. From the mechanical analysis, P3H5 shows the best composite in term of mechanical properties and are chosen for further investigatio n. The incorporation of n-HA did not improve polymer blends' thermal stability; furthermore, the composite’s decomposition temperature was reduced. However, the addition of n-HA has enhanced the transition temperature of the composite. The formation of apatite layers that cover the composite's surface revealed good bioactivity properties of PCL/PLA/PEG/n-HA composite. The optimum parameter setting to produce 1.75+0.05mm of P3H5 filament wire was successfully found at an inlet temperature of 84.55°C, die temperature of 82.35°C, screw speed of 7.43 Hz, and roller speed of 5.87 rpm. This filament wire is of the right size and strength and can be extruded using FDM.